ANALISIS PEMASARAN NENAS PALEMBANG (KASUS: DESA PAYA BESAR, KECAMATAN PAYARAMAN, KABUPATEN OGAN ILIR, PROVINSI SUMATERA SELATAN) - Herawati, Herawati; Rifin, Amzul (Forum Agribisnis, 2013)
Pineapple is one of the commodities that make a significant contribution to the Gross National Product (GDP) Indonesian horticulture. South Sumatra is one of the provinces that have a high volume of pineapple production. Pineapple production center is located in Ogan Ilir regency. There are problems in the marketing of pineapples that affect farmers income. The problem is the high margin difference between farmers and consumers. Therefore, this study aimed to analyze marketing system of pineapples in Paya Besar sub regency. This study used structural approach, conduct approach and market performance. Based on the analysis, there are three channels of pineapple marketing in Paya Besar sub regency. Every channel has different marketing areas. The third channel is more efficient than the other channels. These channel involves farmers, traders village, local wholesalers, and foreign wholesalers. The third channel has the smallest margin, the largest farmers share and the most equitable spread of benefit cost ratio. In addition, sales volume pineapple third channel is the highest volume and most widely used by farmers.